2017
DOI: 10.1002/chem.201605906
|View full text |Cite
|
Sign up to set email alerts
|

Low Bandgap Bistetracene‐Based Organic Semiconductors Exhibiting Air Stability, High Aromaticity and Mobility

Abstract: The benchmark of soluble organic semiconductors based on acenes is the 6,13-bis(triisopropylsilylethynyl)pentacene (TIPS-PEN). However TIPS-PEN still suffers from photoinduced oxidation due to its low degree of aromaticity. Increasing the aromaticity while keeping similar optical and electrochemical properties as well as a shape suitable for good hole transport can be achieved with two-dimensional polycyclic aromatic hydrocarbons (2D-PAHs). Herein, we present an efficient synthesis and characterization of bist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Structure analysis of highly insoluble pristine NGs is evolving as major problem in modern nanographene sciences. Therefore, solubilizing groups are typically attached to the PAH’s skeleton, leading inevitably to an alteration of its original characteristics 28 30 , 32 . Spectroscopically at the border of solubility for NMR analysis, we elucidated the 1 H NMR spectrum of DBATT , obtained at 100 °C in o -DCB (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Structure analysis of highly insoluble pristine NGs is evolving as major problem in modern nanographene sciences. Therefore, solubilizing groups are typically attached to the PAH’s skeleton, leading inevitably to an alteration of its original characteristics 28 30 , 32 . Spectroscopically at the border of solubility for NMR analysis, we elucidated the 1 H NMR spectrum of DBATT , obtained at 100 °C in o -DCB (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Keywords that highlight acene-type PAHs with zig-zag periphery range from singlet fission 17 21 , auspicious charge carrier mobilities 22 , 23 , to amplified spontaneous emission 24 , and enlarge the interest in PAHs by the fields of spintronics and molecular magnetism 25 - 27 . Recently, various research groups reported on substituted angularly fused-tetracenes 28 32 , which overcome the low stability of linear acenes, by increasing the intrinsic number of Clar’s-sextets 33 . These fused structures showed excellent performances in field-effect transistors 28 , 29 , 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It's amazing that both 2D thienoacenes exhibited exceptionally high photostability with a half‐life time ( t 1/2 ) of 226 days for BTT‐4TIPS and 129 days for BTP‐4TIPS under air (Table S2, Figure ). Taking the simple structural consideration, the high stability might be attributed to the aromaticity of the bisthienoacene, which is comparable to an anthrancene along each thienoacene . The excited‐state properties of BTT‐4TIPS and BTP‐4TIPS were further investigated using the fs and ns transient absorption (TA) spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the chemical structures of natural anthocyanins and artificial π‐expanded xanthenium cations, we inferred that pyranyl and pyrylium rings could be used to prepare the O‐doped derivatives of PAHs 1 C – 3 C and to engineer p ‐type organic semiconductors. Out of the three PAHs 1 C – 3 C (Figure , top), attention has been paid only to dibenzanthanthrene ( 1 C ) and its derivatives, with applications in single‐molecule transistors, optical interaction with alkali atoms for quantum memory, as a single emitter for super‐resolution microscopy, and semiconductors with high mobility in solution‐processed OFETs …”
Section: Introductionmentioning
confidence: 99%